Differential effects of biocompatible peritoneal dialysis fluids on human mesothelial and endothelial cells in 2D and 3D phenotypes - Jagirdar, Rajesh M.; Pitaraki, Eleanna; Rouka, Erasmia; Papazoglou, Eleftherios D.; Bartosova, Maria; Zebekakis, Pantelis; Schmitt, Claus P.; Zarogiannis, Sotirios G.; Liakopoulos, Vassilios (Artificial organs, 2024)
Introduction Peritoneal dialysis (PD) is a life maintaining treatment in patients with end-stage renal disease. Its chronic application leads to peritoneal mesothelial layer denudation and fibrotic transformation along with vascular activation of inflammatory pathways. The impact of different PD fluids (PDF) on mesothelial and endothelial cell function and repair mechanisms are not comprehensively described. Materials and Methods Mesothelial (MeT-5A) and endothelial cells (EA.hy926) were cultured in 1:1 ratio with cell medium and different PDF (icodextrin-based, amino acid-based, and glucose-based). Cell adhesion, cell migration, and cell proliferation in 2D and spheroid formation and collagen gel contraction assays in 3D cell cultures were performed. Results Cell proliferation and cell-mediated gel contraction were both significantly decreased in all conditions. 3D spheroid formation was significantly reduced with icodextrin and amino acid PDF, but unchanged with glucose PDF. Adhesion was significantly increased by amino acid PDF in mesothelial cells and decreased by icodextrin and amino acid PDF in endothelial cells. Migration capacity was significantly decreased in mesothelial cells by all three PDF, while endothelial cells remained unaffected. Conclusions In 3D phenotypes the effects of PDF are more uniform in both mesothelial and endothelial cells, mitigating spheroid formation and gel contraction. On the contrary, effects on 2D phenotypes are more uniform in the icodextrin and amino acid PDF as opposed to glucose ones and affect mesothelial cells more variably. 2D and 3D comparative assessments of PDF effects on the main peritoneal membrane cell barriers, the mesothelial and endothelial, could provide useful translational information for PD studies.
Gesehen am 11.03.2024